XeNA: an automated ‘open-source’ 129Xe hyperpolarizer for clinical use - Nikolaou, Panayiotis; Coffey, Aaron M.; Walkup, Laura L.; Gust, Brogan M.; Whiting, Nicholas; Newton, Hayley; Muradyan, Iga; Dabaghyan, Mikayel; Ranta, Kaili; Moroz, Gregory D.; Rosen, Matthew S.; Patz, Samuel; et al. (Elsevier, 2014)
Here we provide a full report on the construction, components, and capabilities of our consortium’s “open-source” large-scale (~ 1 L/h) 129Xe hyperpolarizer for clinical, pre-clinical, and materials NMR/MRI (Nikolaou et al., Proc. Natl. Acad. Sci. USA, 110, 14150 (2013)). The ‘hyperpolarizer’ is automated and built mostly of off-the-shelf components; moreover, it is designed to be cost-effective and installed in both research laboratories and clinical settings with materials costing less than $125,000. The device runs in the xenon-rich regime (up to 1800 Torr Xe in 0.5 L) in either stopped-flow or single-batch mode—making cryo-collection of the hyperpolarized gas unnecessary for many applications. In-cell 129Xe nuclear spin polarization values of ~ 30%–90% have been measured for Xe loadings of ~ 300–1600 Torr. Typical 129Xe polarization build-up and T1 relaxation time constants were ~ 8.5 min and ~ 1.9 h respectively under our spin-exchange optical pumping conditions; such ratios, combined with near-unity Rb electron spin polarizations enabled by the high resonant laser power (up to ~ 200 W), permit such high PXe values to be achieved despite the high in-cell Xe densities. Importantly, most of the polarization is maintained during efficient HP gas transfer to other containers, and ultra-long 129Xe relaxation times (up to nearly 6 h) were observed in Tedlar bags following transport to a clinical 3 T scanner for MR spectroscopy and imaging as a prelude to in vivo experiments. The device has received FDA IND approval for a clinical study of chronic obstructive pulmonary disease subjects. The primary focus of this paper is on the technical/engineering development of the polarizer, with the explicit goals of facilitating the adaptation of design features and operative modes into other laboratories, and of spurring the further advancement of HP-gas MR applications in biomedicine.